Shadow Fleets: A Growing Challenge in Global Maritime Commerce - Emilio Rodriguez-Diaz; Juan Ignacio Alcaide; Nieves Endrina (Applied Sciences)
Shadow fleets, operating covertly in global maritime commerce, have emerged as a significant challenge to international regulatory frameworks and trade policies. This paper introduces a novel conceptual framework that distinguishes between ‘dark fleets’ and ‘gray fleets’, offering a more nuanced understanding of these clandestine maritime activities. Through a comprehensive methodological approach integrating a literature review, case studies, and data analysis, we examine the characteristics, operational strategies, and implications of shadow fleets. Our research reveals that shadow fleets have expanded rapidly, now accounting for approximately 10% of global seaborne oil transportation. We identify key indicators of shadow fleet operations, including disabled Automatic Identification System (AIS) transmitters, inconsistent vessel information, unusual behavior patterns, obscure ownership structures, and the use of aging vessels. This paper highlights the economic disruptions caused by shadow fleets, their role in circumventing international sanctions, and the significant environmental and safety risks they pose. The study underscores the regulatory challenges in addressing shadow fleets, particularly their exploitation of flags of convenience and complex ownership structures. We propose a multifaceted approach to tackling these challenges, emphasizing the need for advanced technological solutions, enhanced international collaboration, and adaptive ocean governance frameworks. This research contributes to the evolving field of maritime security and policy, offering insights for policymakers, industry stakeholders, and researchers into developing strategies to mitigate the risks posed by shadow fleets in global maritime commerce.